Low temperature conversion of levulinic acid into γ-valerolactone using Zn to generate hydrogen from water and nickel catalysts supported on sepiolite. Issue 35 (27th May 2020) - García, Adrián; Sanchis, Rut; Miguel, Pablo J.; Dejoz, Ana M.; Pico, María Pilar; López, María Luisa; Álvarez-Serrano, Inmaculada; García, Tomás; Solsona, Benjamín
Abstract : Levulinic acid transformation into γ-valerolactone at 30 °C in water without molecular hydrogen addition. Abstract : In the present article, γ-valerolactone has been obtained from levulinic acid with a yield exceeding 25% using very mild conditions without feeding hydrogen (30 °C, atmospheric pressure, water as the hydrogen source). The overall reaction conducted is a two-step process: first, a redox reaction involving the oxidation of metallic Zn to ZnO for in situ hydrogen production through the water splitting reaction and, second, a catalytic reaction involving Ni-supported catalysts for the production of γ-valerolactone from levulinic acid. Ni active sites have been supported on sepiolite, an abundant and cheap material. The nickel particle size has been demonstrated to be a parameter of paramount importance determining the catalytic activity, since the best catalytic performance is obtained with the smallest Ni nanoparticles. This combination of Zn and Ni supported on sepiolite shows a good catalytic stability after three catalytic runs.